Web-Based Students Assessment System for Efficient Assessment - Emily, Nordini (Multidisciplinary Applied Research and Innovation, 2023)
Education is the most significant aspect of our life since it provides us with information in a variety of areas. In 2015, 195 nations agreed with the United Nation that they can change the world for the better. Following Sustainable Development Goal 4, highlights the importance of quality of education. According to the interview, the previous systems that used web-based platforms, Sistem Analisis Peperiksaan Sekolah (SAPS), experienced problems such as website closures during the Covid-19 pandemic, which had a significant impact on teachers in placing student’s school marks and results and displaying them online. The usage of Excel software to replace the SAPS system results in duplicate student information and inaccurate student score information. Therefore, the e-Student Assessment System was created to assist Sekolah Kebangsaan Kota Raja in overcoming the challenges of handling student information, and scores, and generating school performance on an online platform. The e-Student Assessment System attempts to reduce the challenges that instructors have while utilizing traditional methods. The system was created using a waterfall model as the development technique. After the project, instructors will be able to manage and display their students' school performance in an orderly and effective manner. A survey was conducted, and the majority of those who responded believed that this approach aids and facilitates instructors. It is believed that this system would give schools management tools and improve instructor quality services.